Modified dose of melphalan-prednisone in multiple myeloma patients receiving bortezomib plus melphalan-prednisone treatment - Se Ryeon Lee; Hojoon Choi; Byung Hyun Lee; Ka-Won Kang; Eun Sang Yu; Dae Sik Kim; Yong Park; Chul Won Choi; Byung Soo Kim; Hwa Jung Sung (The Korean Journal of Internal Medicine, 2019)
Background/Aims Bortezomib plus melphalan-prednisone (VMP) is a standard treatment for multiple myeloma, particularly for patients who are ineligible for high-dose therapy. However, early discontinuation or treatment modification is often needed owing to adverse events. The aim of this study was to investigate the clinical outcomes of modifying the dose of melphalan-prednisone (MP) in patients receiving VMP. Methods We examined 67 patients who received a modified dose of MP, and 38 patients who received the regularly planned dose of MP. We then analyzed clinical differences between the groups. Results Although there was no difference in the proportion of discontinuation due to adverse events between dose groups, more patients in the planned-dose group experienced earlier discontinuation in general. The overall response rate (ORR) was 81.0% and complete response (CR) rate was 30.5%. After a median 15.7 months of follow-up, the median progression-free survival (PFS) and overall survival (OS) were 25.0 and 47.8 months, respectively. There was no significant difference in the ORR, CR, PFS, and OS of the two dose groups. A median of four cycles were delivered, and the median cumulative bortezomib dose was 41.6 mg/m2 . The median PFS in patients with doses ≥ 41.6 mg/m2 was longer than that in patients with doses < 41.6 mg/m2 (35.1 months vs. 9.6 months). However, when MP was < 50% of the planned dose, PFS and OS were poor. Conclusions Modifying the dose of MP might be a feasible and effective therapeutic approach for multiple myeloma patients receiving VMP treatment.